FEATURES OF THE PHACOEMULSIFICATION TECHNIQUE OF CATARACT IN PSEUDOEXFOLIATION SYNDROME - E. V. Egorova (Сибирский научный медицинский журнал, 2019)
Traditional surgery of cataract in pseudoexfoliation syndrome (PEX) can be excessively aggressive and increase zonular instability. The main technological target of this surgery is reducing of a zonular stress at all stages and especially when removing the lens nucleus. Purpose was to develop an effective and safe technique for nucleus removal without rotating crystalline lens during phacoemulsification in PEX. Material and methods. 765 eyes with PEX were treated by phacoemulsification without nuclear rotation using original technique. The left paracentral oblique groove was made after capsulotomy and hydrodissection. Nucleus was divided by phaco tip and chopper. In right heminucleus a lateral deep groove was performed such way to create a big asymmetric wedge including central part of nucleus. This wedge was removed without rude manipulation and rotation. The remaining two peripheral segments were easily gripped and pull into pupil area for safe phacoemulsification. Results. In all cases this technique allowed for safe removing of the nucleus. Cataract surgery was finished without serious intraoperative complications. Conclusion. This method allows reducing intraoperative zonular stress and removing all nucleus fragments in the conditions of limited mydriasis at the maximum distance from the corneal endothelium. The rotationless technology of nucleous removal is effective and safe at cataract in PEX.